2018
DOI: 10.1038/s41419-017-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/mTOR inhibition promotes the regression of experimental vascular malformations driven by PIK3CA-activating mutations

Abstract: Somatic activating mutations within the PIK3CA gene have been recently detected in sporadic lymphatic and venous malformations, and in vascular malformations (VM) associated to overgrowth syndromes, such as CLOVES and Klippel–Trenaunay syndrome. Although VM are often limited to specific tissue areas and can be well treated, in extended or recurrent lesions novel therapeutic approaches are needed. We generated a mouse model of VM by local expression of PIK3CA-activating mutation in endothelial cells. PIK3CA-dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 38 publications
4
72
0
3
Order By: Relevance
“…; di Blasio et al. ). Vascular malformations share several functional deficits with other vascular diseases including hypercoagulation, vascular remodeling, endothelial senescence, and inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; di Blasio et al. ). Vascular malformations share several functional deficits with other vascular diseases including hypercoagulation, vascular remodeling, endothelial senescence, and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it also serves as a central hub of signal integration of numerous protein kinases including AMPK, CAMKII, as well as AKT. Recently, vascular malformations arising from mutations in PIK3CA have been shown to be sensitive to rapamycin treatment in mice as well as humans (Limaye et al 2015;Castel et al 2016;di Blasio et al 2018). Vascular malformations share several functional deficits with other vascular diseases including hypercoagulation, vascular remodeling, endothelial senescence, and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the presence of somatic ‘second hits’ in TIE2 in lesions of VMCM patients, as a loss ‐ of ‐ function deletion mutation in trans (deleting a possibly protecting WT allele) or as a second missense mutation in cis , likely potentiating the gain ‐ of ‐ function effect of relatively weaker inherited mutations when compared to mutations found alone in sporadic VMs . On the other hand, TIE2 ‐ L914F, TIE2 double mutations or PIK3CA mutations have never been found as inherited, suggesting that they all are lethal in germline, as already shown for PIK3CA ‐ H1049R using genetic mouse models .…”
Section: Genetic Cause Of Vms and Subtypesmentioning
confidence: 98%
“…) . In addition, both VM EC transplantation studies and use of EC ‐ specific Cre drivers together with inducible VM mutations have indicated that TIE2 or PIK3CA mutation in an EC compartment is sufficient for VM lesion formation . Disease mechanisms downstream from a mutated TIE2/PIK3CA are not completely understood.…”
Section: Molecular and Cellular Pathology Of Vmsmentioning
confidence: 99%
See 1 more Smart Citation